Dividends, Short Selling Restrictions, Tax-Induced Investor Clienteles and Market Equilibrium: Discussion - Hess, Patrick J. (Journal of Finance, 1980)
Patrick J. Hess, Dividends, Short Selling Restrictions, Tax-Induced Investor Clienteles and Market Equilibrium: Discussion, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 482-485